Alternative Dispute Resolution on Consumer Conflicts in the EU and Turkey - Esra Ünal (Ankara Avrupa Çalışmaları Dergisi)
Consumer conflicts arise every day, and how to handle this issue is a major part of ensuring consumer redress mechanisms. In the 1970s, alternative dispute resolution (ADR) methods were adopted in response to an increase in consumer conflicts, with the aim of reducing the workload on courts. ADR has been supported by the European Union (EU), which enacted the 2013/11/EU ADR Directive to standardize consumer redress mechanisms between Member States. However, because of the general nature of the provisions, there have been many different approaches and methods in the member states. It has also become imprecise to understand if it is a good role model or effective because of the ambiguous provisions and various approaches. Turkish Law on Consumer Protection entered into force in 2014 to ensure the harmonisation duty of the EU acquis, and it regulated the sui generis procedure of Consumer Arbitration Committees (CAC) and then compulsory mediation on consumer conflicts with an added article in 2020. This article argues that CAC is harmonised with the EU acquis and ADR systems in Turkey, bringing more effective consumer redress mechanisms for now due to cultural and economic reasons, even if it is not perfect and has to be improved.